An educational strategy for improving knowledge about breast and cervical cancer prevention among Mexican middle school students - Calderón Garcidueñas, Ana Laura; Flores Peña, Yolanda; De León Leal, Silvia; Vázquez Martínez, Carlos Alberto; Farías Calderón, Ana Gabriela; Melo Santiesteban, Guadalupe; Elizondo Zapién, Rosa María; Hernández Hernández, Dulce María; Garza Moya, Rubén; Cerda Flores, Ricardo Martín (Elsevier, 2015)
Introduction: Prevention programs have not achieved the expected results in preventing mortality from breast and cervical cancer in Mexico. Therefore, we propose a complementary strategy. Methodology: An educational strategy for high school students in Mexico (2011–2013) was designed (longitudinal design, two measurements and a single intervention). The postintervention assessment included: 1) knowledge acquired by students about cancer prevention and 2) The performance of the student as a health promoter in their household. The strategy was based on analysis of cases and developed in three sessions. An assessment tool was designed and validated (Test–Retest). The levels of knowledge according to the qualifications expected by chance were determined. Wilcoxon test compared results before and after intervention. Results: An assessment instrument with 0.80 reliability was obtained. 831 high school students were analyzed. Wilcoxon rank-sum test showed a significant learning after the intervention (Z = −2.64, p = 0.008) with improvement of levels of knowledge in a 154.5%. 49% of students had a good performance as health promoters. Conclusions: The learning in preventive measures is important to sensitize individuals to prevention campaigns against cancer. This strategy proved to improve the level of knowledge of students in an easy and affordable way.